Infografis sebagai Media Edukasi di Museum Brawijaya: Studi Kasus pada Koleksi Arsip Operasi Trisula - Izzatul Ulya; Nunung Aliyati Fajer; Diana Eka Poernamawati; Ratnaning Palupi; Muhammad Iqbal; Mareta Ardiani (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the role of infographics as an educational medium in presenting historical archives at the Brawijaya Museum, focusing on the 1968 Operation Trisula archive collection. The research method used is a qualitative case study approach, involving direct observation, interviews with museum managers, and document analysis. Data triangulation was applied to maintain the validity of the study. The results show that the use of infographics increases visual appeal, makes it easier for visitors to understand the historical context of Operation Trisula, and strengthens the educational experience at the museum. Visitor responses were generally positive, marked by increased interaction, interest, and understanding of the archives displayed. This study concludes that infographics are a strategic medium in historical archive education, because they are able to combine elements of information, visualization, and educational value that are relevant to the community. Keywords: Brawijaya Museum, Infographics, Operation Trisula Archives.